Effect of Enhanced Electron Withdrawal on the Cohesion of Cr‐Pd Hemichelates. Issue 28 (17th July 2019) - Werlé, Christophe; Karmazin, Lydia; Bailly, Corinne; Djukic, Jean‐Pierre
Abstract : Two new trimetallic Cr‐Pd hemichelates containing a fluorenyl moiety and two trans arene‐bound Cr(CO)3 moieties were synthesized and fully characterized. Their molecular structures obtained by X‐ray diffraction analysis do not show major differences – in interatomic bond lengths within the Pd coordination sphere – when compared to previously reported bimetallic analogues. Theoretical investigations were performed using methods of the Density Functional Theory (ZORA‐PBE‐D3(BJ)/all electron TZP level, EDA, ETS‐NOCV and QTAIM‐IQA) to analyse the influence of a second Cr(CO)3 moiety in the process of formation of the Cr‐Pd hemichelate. Theory shows that despite the extensive charge delocalization in the anion of trans‐bistricarbonylchromium(fluorene), the formation of a stable hemichelate is still possible albeit requiring a moderate energy payload to funnel charge density towards the formation of the benzylic carbon–palladium bond. IQA analyses of hemichelates show the important role of attractive electrostatic interactions in the dominantly noncovalent Cr(CO)3 ‐Pd interactions. Abstract : In spite of the presence of two electron‐withdrawing Cr(CO)3 moieties on the trans‐bistricarbonylchromium(fluorenyl) anion, the formation of a stable heterotrimetallic Pd(II) hemichelate remains possible. Theory suggests that the cohesive hemichelate results from a major charge density relocation from the delocalized anion to the benzylic carbon–Pd bond.